Endovascular correction of isolated descending thoracic aortic disease: a descriptive analysis of 1,344 procedures over 10 years in the public health system of São Paulo (Clinics, 2021)
OBJECTIVES: In Brazil, descending thoracic aorta disease (TAD), including aneurysms and dissection, are preferentially managed by endovascular treatment (TEVAR) due to the feasibility and good results of this technique. In this study, we analyzed endovascular treatment of isolated TAD (ITAD) in the public health system over a 10-year period in Sa˜o Paulo, a municipality in Brazil in which more than 5 million inhabitants depend on the governmental health system. METHODS: Public data from procedures performed between 2008 and 2019 were extracted using web scraping techniques. The following types of data were analyzed: demographic data, operative technique, elective or urgent status, number of surgeries, in-hospital mortality, length of hospital stay, mean length of stay in the intensive care unit, and reimbursement values paid by the government. Trauma cases and congenital diseases were excluded. RESULTS: A total of 1,344 procedures were analyzed; most patients were male and aged X65 years. Most individuals had a residential address registered in the city. Approximately one-third of all surgeries were urgent cases. There were 128 in-hospital deaths (9.52%), and in-hospital mortality was lower for elective than for urgent surgeries (7.29% vs. 14.31%, p=0.031). A total of R$ 24.766.008,61 was paid; an average of R$ 17.222,98 per elective procedure and R$ 18.558,68 per urgent procedure. Urgent procedures were significantly more expensive than elective surgeries (p=0.029). CONCLUSION: Over a 10-year period, the total cost of ITAD interventions was R$ 24.766.008,61, which was paid from the governmental system. Elective procedures were associated with lower mortality and lower investment from the health system when compared to those performed in an urgent scenario.